Samuel Bogumił Linde w dziejach recepcji twórczości Nikołaja Karamzina (wokół polskiego przekładu Rysu historycznego literatury rosyjskiej Nikołaja Grecza) - Dąbrowska, Magdalena (Acta Polono-Ruthenica, 2019)
The paper presents annex no. 1 to the Historical background of the Russian literatureby Nikolay Gretsch, translated and edited by Samuel Bogumił Linde (Warszawa, 1823). The annex, entitled About the story “The Igor’s Campaign” by Karamzin, is a translation of the excerpt from the History of the Russian state (chap. 7, vol. III), which was published in another work of Gretsch, the Scientific book of the Russian literature (vol. 1–4, Saint-Petersburg, 1819–1822). It concerns the masterpiece of the Old-Russian literature The Tale of Igor’s Campaign. The paper presents the place of Karamzin’s work in the structure of the Polish edition of the “Historical background of the Russian literature”. An interpretive context is Linde’s correspondence with Vasily Anasta-syevitch.